Connecting with Future Talent: A Review of Employer Value Propositions and Digital Media Channels for Sustainable Companies Targeting Generations Y and Z - Kristia (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: This literature review aims to provide a comprehensive understanding of the employer value proposition of ethical and sustainable companies and the effective digital media channels that sustainable companies can use to attract and communicate with Generation Y and Z candidates. Design/Methods/Approach: The PRISMA systematic literature review method was combined with content analysis of selected articles from the Scopus and Web of Science databases. The selected articles were limited to those published within the last six years and in English. Findings: This study found that sustainable companies need to offer a corporate value proposition that prioritizes clear career progression, work-life balance, a supportive work atmosphere, and ethical aspects, such as reducing carbon footprint and promoting diversity and inclusion. These values are essential to Generations Y and Z, although the priority dimensions of their value propositions may differ. Companies utilize Digital media channels, including owned digital media, paid digital media by using paid endorsers or enhanced profiles on career websites, and earned digital media such as honest reviews on job board platforms and private social media from employees. Originality/Value: This review adds to the existing literature by comprehensively discussing the combined issues of employer value proposition, generational differences, and sustainability. Practical/Policy implication: This review's findings have implications for business and research practice, as sustainable companies can use this information to develop the most relevant corporate value propositions and communication strategies for future targeted talent. Companies can attract and retain top personnel and establish a positive employer brand by effectively communicating their sustainability practices and values. Additional empirical research could investigate the impact of other demographic and psychographic factors on the preferences and priorities of job seekers.